Echoanatomical Features of the Major Cervical Blood Vessels of the Juvenile Green Sea Turtle (Chelonia mydas) - Justo, André Augusto (2022)
Although ultrasonographic examination of the blood vessels of sea turtles has been a helpful tool in the clinical setting, there is a paucity of data on the normal cervical echoanatomy of green turtles (Chelonia mydas); such information could be valuable for conservation-focused efforts at rehabilitation facilities. We studied the echoanatomical features of the major blood vessels of the neck of juvenile green turtles by gross dissection of 5 deceased turtles and by ultrasonographic examination of 11 healthy animals. The external jugular and the vertebral veins were superficial (< 1.5 cm) and presented an echogenic and turbulent pattern of blood flow in B-mode examination; carotid arteries lied deeply within the neck (> 1.5 cm) and exhibited a laminar blood flow characterized by a parabolic velocity profile as determined by Doppler sonography.